Enhancing Learning Creativity and Computational Thinking through Coding-Based Flipbook Media in Elementary Education - Listyana, I Gusti Agung Ayu Putu; Suarjana, I Made; Antara, Putu Aditya (Journal of Education Technology, 2024)
This study addresses the issue of low learning motivation, limited student understanding of science concepts, and the lack of diverse instructional media in fifth-grade elementary classrooms. These conditions necessitate solutions through interactive and innovative learning approaches. The research aims to design, evaluate the validity, practicality, and effectiveness of coding-based flipbook learning media to enhance students’ learning creativity and computational thinking skills. This study employs a quantitative design using a pretest-posttest control group model. The research subjects consist of 36 fifth-grade students. Data were collected through a learning creativity questionnaire and a computational thinking test. Data analysis was conducted using inferential t-tests to determine significant differences between experimental and control groups. The findings reveal that coding-based flipbook media exhibit high validity and practicality levels and are significantly effective in improving students’ learning creativity and computational thinking skills. These findings provide a relevant solution to the issues of low learning motivation, limited concept understanding, and inadequate instructional media in the classroom. In conclusion, coding-based flipbook media represent an effective and innovative approach to supporting science education in elementary schools.